PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMEN BERBANTU MEDIA PUZZLE FLANEL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V - Bakda Mauludy, Nabilla; Widiyanto, Joko; Iswanto, Iswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Science is one of the subjects at elementary school (SD) level, which studies important events in nature by studying living things and the surrounding environment. The results of initial observations at SDN Kandangan 1 Ngawi, problems with Class V science learning have been revealed. This problem arises because teachers' skills are not yet optimal and there is a lack of variety in learning methods and use of media, resulting in low student activity and low learning outcomes. students who have not completed their learning objectives. This research aims to improve students' science and science learning outcomes on food chains in terrestrial ecosystems, through cooperative learning standards of the Teams Games Tournament (TGT) type assisted by flannel puzzle media for grade V elementary school students. This type of research is Classroom Action Research (PTK). ). The subjects in this research were class V students at SDN Kandangan 1 Ngawi Regency with a total of 17 children. Data collection techniques in this research were observation, tests and documentation. The research data analysis technique uses quantitative and qualitative descriptive analysis. The results of research on the Teams Games Tournament (TGT) type cooperative learning model assisted by flannel puzzle media showed that there was a significant increase in each cycle. This is proven by the pre-cycle or before using the TGT type cooperative learning model assisted by flannel puzzle media. It is known that only 5.88% of students or the equivalent of 1 child have achieved the aim of learning science and technology on terrestrial ecosystem food chains. Furthermore, in cycle 1 there was a significant increase in learning outcomes as evidenced by 52.94% of students or the equivalent of 9 children having achieved the learning objectives. Continuing in the second cycle, learning outcomes also increased, amounting to 82.35% or the equivalent of 14 students having achieved this learning objective.